2019
DOI: 10.1038/s41598-019-55079-w
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal obstructive nephropathy induces necroptosis and necroinflammation

Abstract: Urinary tract obstruction during kidney development causes tubular apoptosis, tubular necrosis, and interstitial inflammation. Necroptosis is a subtype of programmed necrosis mediated by the receptor-interacting serine/threonine-protein kinase-3 (RIPK3) and the pseudokinase mixed lineage kinase domain-like (MLKL). Necrosis induces inflammation and stimulates cell death in an autoamplification loop named necroinflammation. Here, we studied necroptosis and necroinflammation in obstructive nephropathy induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 52 publications
3
35
0
Order By: Relevance
“…IL-33 is able to activate basophils and eosinophils, as well as to induce type 2 immune responses (58). Recently it was shown that necroptosis and necroinflammation are accompanied phenomena in neonatal kidneys with ureteral obstruction (17). Biochemical analyses showed a decrease in caspase-8 expression and an increase in RIPK3 and pMLKL expression, indicating a role of necroptosis in UUO.…”
Section: Il-1a and Il-33mentioning
confidence: 99%
“…IL-33 is able to activate basophils and eosinophils, as well as to induce type 2 immune responses (58). Recently it was shown that necroptosis and necroinflammation are accompanied phenomena in neonatal kidneys with ureteral obstruction (17). Biochemical analyses showed a decrease in caspase-8 expression and an increase in RIPK3 and pMLKL expression, indicating a role of necroptosis in UUO.…”
Section: Il-1a and Il-33mentioning
confidence: 99%
“…As UMOD accumulation within renal tubules has been reported during normal neonatal development, we investigated UMOD expression in neonatal kidneys after unilateral ureteral obstruction (UUO) thereby linking a potential accumulation of UMOD at extratubular sites to leukocyte infiltration, which is commonly observed in neonatal UUO (37,38). First, we performed Western Blot analysis in sham (control) and UUO operated neonatal kidneys.…”
Section: Neonatal Obstructive Nephropathy Induces Intra-and Extratubumentioning
confidence: 99%
“…UMOD is highly expressed in the developing kidney and urinary tract obstruction during kidney development leads to leukocyte recruitment, inflammation and interstitial fibrosis in the neonatal kidney (37,54). Therefore, we investigated UMOD expression, localization and immune cell infiltration in a neonatal model of unilateral ureteral obstruction (UUO).…”
Section: Neonatal Obstructive Nephropathy Induces Intra-and Extratubumentioning
confidence: 99%
See 2 more Smart Citations